Sweden : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper for Sweden reports that the gradual introduction of a detailed fiscal framework accompanied the successful consolidation effort over the last decade in Sweden. The framework includes a surplus target of 2 percent of GDP for the general government, multiyear expenditure ceilings for central government, and a balanced budget requirement for local governments. Reliance on the expertise of an independent agency for the implementation of the fiscal framework could further enhance transparency and strengthen enforcement.